Fractional laser for vitiligo treated by 10 600 nm ablative fractional carbon dioxide laser followed by sun exposure. Issue 6 (30th May 2014) - Hélou, J.; Maatouk, I.; Obeid, G.; Moutran, R.; Stéphan, F.; Tomb, R.
<x xml:space="preserve">Abstract</x> Background Vitiligo is an acquired disorder of the skin and mucous membranes. Many patients with vitiligo remain in the refractory state despite the availability of numerous potential treatments. To the best of our knowledge, only one trial considers ablative fractional CO2 laser in the treatment of vitiligo. Objective To investigate the effects of fractional CO2 laser followed by systemic sun exposure on non‐segmental vitiligo (NSV). Methods Ten patients presenting refractory NSV were enrolled in this study. The patients underwent three sessions, one month apart, of fractional CO2 laser therapy on the affected areas of the skin (L‐group). Five days after each laser treatment, patients were asked to expose themselves to the sun for 2 hours on a daily basis. Objective and subjective clinical assessments were performed at the beginning and at the end of the treatment. The L‐group was then compared to a control group (C‐group) that consisted of vitiligo lesions in the same patients but with sun exposure as the exclusive therapy. Results Compared to the C‐group, the L‐group showed better improvement in both objective and subjective assessments. There were no noticeable adverse events in terms of scarring and Koebner phenomenon among others. Conclusions All patients treated with both, laser sessions and sun exposure, improved their chronic NSV lesions. Improvement was less significant in patients who exhibited vitiligo lesions over articular surfaces such as elbows and underarms. The best results were observed in vitiligo plaques located on the face, neck and legs. Consequently, fractional CO2 laser followed by sun exposure could be considered as an alternative modality for the treatment of refractory vitiligo, especially in sunny regions. Lasers Surg. Med. 46:443–448, 2014. © 2014 Wiley Periodicals, Inc.